2021
DOI: 10.1073/pnas.2022912118
|View full text |Cite
|
Sign up to set email alerts
|

Aggression heuristics underlie animal dominance hierarchies and provide evidence of group-level social information

Abstract: Members of a social species need to make appropriate decisions about who, how, and when to interact with others in their group. However, it has been difficult for researchers to detect the inputs to these decisions and, in particular, how much information individuals actually have about their social context. We present a method that can serve as a social assay to quantify how patterns of aggression depend upon information about the ranks of individuals within social dominance hierarchies. Applied to existing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
133
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(145 citation statements)
references
References 56 publications
8
133
2
2
Order By: Relevance
“…Such findings contrast with the very similar patterns observed across our two groups (different only in low-cost aggressive interactions among dyads with large rank differences and corresponding to low data densities) and in two social groups of monk parakeets [19]. Variation in strategies could appear from differences in the types of resources that individuals compete for [20], or if studies are conducted in different contexts.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Such findings contrast with the very similar patterns observed across our two groups (different only in low-cost aggressive interactions among dyads with large rank differences and corresponding to low data densities) and in two social groups of monk parakeets [19]. Variation in strategies could appear from differences in the types of resources that individuals compete for [20], or if studies are conducted in different contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have suggested that rank differences may underlie patterns of aggressive interactions in group-living species [19,20]. Here, we extend current methods to incorporate dyadic opportunity to interact and-using an agent-based model-demonstrate that, if unaccounted for, such differences in opportunity can drive patterns that appear to be strategic (i.e.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations